Introduction to AI for medical imaging - McMillan, Alan B. (Henry Stewart Talks, 2023)
AI vs. ML vs. DL, The machine learning paradigm, Supervised vs. unsupervised learning, Machine learning vs. deep learning, Convolutional Neural Networks (CNNs), Segmentation architectures, Vision Transformers (ViTs), Steps to build a machine learning solution, How do we evaluate an AI model, Evaluating performance, Generalizability and bias, Interpretability, Robustness